2021
DOI: 10.5376/tgmb.2021.11.0001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Codon Usage Bias in the <i>Platycarya</i> Chloroplast Genome

Abstract: To detect the codon usage characteristics of chloroplast genomes in Platycarya genus, the CodonW、CUSP and SPSSAU software were employed to analyze the codon usage patterns of the chloroplast genomes protein-coding sequence in Platycarya longipes and Platycarya strobilacea in this research. Results show that the GC content of chloroplast genomes was 37.75% and 37.80%, the average GC content in the 3rd position was 27.16% and 27.25%. the range of effective codon number from 35.19 to 56.98, and there were more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In the chloroplast genomes of the six plants examined in this study, Arg and Leu were found to be more frequently used. Among amino acids with a total codon count below 2,000, Cys exhibited the lowest frequency, aligning with patterns observed in terrestrial plants like Allium mongolicum Regel 66 and Psammosilene tunicoides W.C. Wu et C.Y. Wu 67 .…”
Section: Disscussionsupporting
confidence: 77%
“…In the chloroplast genomes of the six plants examined in this study, Arg and Leu were found to be more frequently used. Among amino acids with a total codon count below 2,000, Cys exhibited the lowest frequency, aligning with patterns observed in terrestrial plants like Allium mongolicum Regel 66 and Psammosilene tunicoides W.C. Wu et C.Y. Wu 67 .…”
Section: Disscussionsupporting
confidence: 77%
“…Analyzing codon usage patterns is important for the study of gene expression levels, protein structures and translation rates in organisms (Wang et al, 2023). Codon usage preference is an adaptive choice formed by species during long-term natural selection and evolutionary processes, which is mainly influenced by gene mutation pressure and natural selection pressure (Sueoka et al, 1988).…”
Section: Gc Content Analysismentioning
confidence: 99%